Innovative approaches in the creation of technologies of dry concentrates cocktails with increased content biologically active substances - Kondratiuk, Natalia Vyacheslavivna; Petukhov, Nikita Olegovich; Suprunenko, Katerinа Evgenievna; Karpenko, Sergiy Oleksandrovich (Національний технічний університет "Харківський політехнічний інститут", 2020)
Modern trends in the creation of drinks provide for the use of various infusions, plant extracts, as well as vitamin and mineral complexes, organic acids and polysaccharides as part of their bases, which allows for the normalization of physiological and metabolic processes in the human body and prevents a number of diseases and syndromes that lead to a decrease in working capacity. The main problems in the creation of various drinking forms are associated with the purification and preparation of water, the dissolution of components and their possible interaction with each other in the packaging unit during storage. Considering the above, it is relevant to create dry concentrates for long-term storage for the preparation of drinks and cocktails as promising drinking forms for normalizing the nutritional status of the population of Ukraine and other countries. It has been established that the physiological value of dry drinks according to the developed method is preserved in ready-made commercial forms (sticks with a metallized substrate) for the entire recommended shelf life – 12 months. The mixture, when diluted, provides the desired functional properties and is a convenient form for transportation and preparation, taking into account the usual dilution with a liquid, mainly drinking water. The novelty of individual technological solutions and the revealed physiologically functional properties lies in the use of extracts of plants, fruits, berries, vegetables with an increased content of biologically active substances, as well as the use of other components that have unique physiotherapeutic properties for humans.

Сучасні тенденції створення напоїв передбачають використання в складі їх основ різних настоїв, екстрактів рослин, а також вітамінномінеральних комплексів, органічних кислот і полісахаридів, що дозволяє забезпечити нормалізацію фізіологічних і метаболічних процесів в організмі людини і запобігти низці захворювань і синдромів, що знижують працездатність. Основні проблеми при створенні різних питних форм пов'язані з очищенням і підготовкою води, розчиненням компонентів і їх можливими взаємодіями в ході зберігання в фасувальній одиниці. З огляду на викладене, актуальним є створення сухих концентратів тривалого зберігання для приготування напоїв та коктейлів в якості перспективних питних форм для нормалізації харчового статусу населення України та інших країн. Встановлено, що фізіологічна цінність сухих напоїв за розробленим способом зберігається в готових товарних формах (стіках з металізованою вкладкою) протягом рекомендованого терміну зберігання – 12 місяців. Суміш при розведенні забезпечує задані функціональні властивості і є зручною формою для транспортування і приготування, враховуючи звичайне розведення рідиною, переважно питною водою. Новизна окремих технологічних рішень і виявлених фізіологічно функціональних властивостей полягає у використанні екстрактів рослин, плодів, ягід, овочів зі збільшеним вмістом біологічно активних речовин, а також використанні інших компонентів, що мають унікальні фізіотерапевтичні властивості для людини.
Інноваційні підходи у створенні технологій сухих концентратів коктейлів з підвищеним вмістом біологічно активних речовин
Keywords: beverages; напої